The Relationship between Media Literacy and Information Processing Ability in 360-degree Video - Aurelia Felicia Bunardi; Albertus Magnus Prestianta (Komunikator, 2023)
Immersive journalism presents information of an event from a first-person perspective to the audience through 360-degree videos that can be watched on smartphones. However, an immersive experience does not guarantee that Gen Z audiences will understand the information conveyed, due to the attraction of short attention spans. Audiences need skills to be able to navigate the media they watch to get the information they consume. Literacy studies on immersive 360-degree video, especially in Indonesia, are still rare. Even though digital media is increasingly immersive in presenting content, it is not known how far young audiences are able to analyze and critically assess the content accessed. This study aims to measure the media literacy level of the audience and its influence on the ability to process 360-degree video. A survey was conducted of 400 students in Jakarta in November 2022. The findings show that the processing capacity of 360-degree videos is significantly affected by a person’s level of media literacy. The better their media literacy ability, the easier it is for someone to process information from 360-degree videos.